Mg-Al layered double hydroxides: A correlation between synthesis-structure and ionic conductivity - Zhang, P.; Yamaguchi, T.; Nair, Balagopal; Miyajima, K.; Anilkumar, G. (Royal Society of Chemistry, 2014)
© the Partner Organisations 2014.Mg-Al based layered double hydroxide (LDH) samples with distinct morphology and crystallinity were synthesized by controlling urea assisted homogeneous precipitation conditions. The obtained samples were characterized with XRD, TG-DTA, FESEM, CHN and XPS analysis and compared with the ionic conductivity values measured at 80 °C under various humidity conditions. The results revealed that LDH particles with small size and low crystallinity were able to adsorb more water resulting in high ionic conductivity. In contrast, LDH particles with large size and high crystallinity showed low ionic conductivity. However, delamination of such highly crystalline LDH particles was found to be an extremely effective method to increase the ionic conductivity. This journal is